Resistensi Urang Banten terhadap Agama Kristen: Sebuah Kajian Teologi Kontekstual - Lumintang, Onnie; Bangun, Grace Yunita Apulina; Andreas, Nasran; Saptono, William Nico (Sekolah Tinggi Teologi Torsina Surakarta, 2025)
The Urang Banten, a Sundanese ethnic group residing in Banten Province, demonstrate significantly greater resistance to Christianity than Sundanese communities in other provinces. This is evidenced by the considerable difficulties in obtaining permits for church construction in Banten Province. This study aims to identify the factors contributing to the Urang Banten's resistance to Christianity. The research employs a literature review methodology examining the history, beliefs, culture, and characteristics of the Urang Banten. Through the research findings, the author postulates that the factors causing Urang Banten's resistance to Christianity are: (1) ancestral cultural and belief systems intertwined with Islamic religious practices that strictly implement sharia law; and (2) the issue of